Stress and Eating Behavior: A Daily Diary Study in Youngsters - Debeuf, Taaike; Verbeken, Sandra; Van Beveren, Marie-Lotte; Michels, Nathalie; Braet, Caroline (Frontiers in Psychology, 2018)
BACKGROUND: Overweight and obesity are growing problems, with more attention recently, to the role of stress in the starting and maintaining process of these clinical problems. However, the mechanisms are not yet known and well-understood; and ecological momentary analyses like the daily variations between stress and eating are far less studied. Emotional eating is highly prevalent and is assumed to be an important mechanism, as a maladaptive emotion regulation strategy, in starting and maintaining the vicious cycle of (pediatric) obesity. OBJECTIVES: The present study aims to investigate in youngsters (10 – 17 years) the daily relationship between stress and the trajectories of self-reported eating behavior (desire to eat motives; hunger eating motives and snacking) throughout one week; as well as the moderating role of emotion regulation and emotional eating in an average weight population. METHOD: Participants were 109 average weighted youngsters between the age of 10 and 17 years (Mage = 13.49; SD = 1.64). The youngsters filled in a trait-questionnaire on emotion regulation and emotional eating at home before starting the study, and answered an online diary after school time, during seven consecutive days. Desire to eat motives, hunger eating motives and snacking were assessed daily for seven consecutive days. RESULTS: Using multilevel analyses results revealed that daily stress is significantly associated with trajectories of desire to eat motives and hunger eating motives. No evidence was found for the moderating role of maladaptive emotion regulation in these relationships; marginally significant evidence was found for the moderating role of emotional eating in the trajectories of desire to eat and snacking. DISCUSSION These results stress the importance of looking into the daily relationship between stress and eating behavior parameters, as both are related with change over and within days. More research is needed to draw firm conclusion on the moderating role of emotion regulation strategies and emotional eating.